Emily and Charlotte Brontë’s Re-reading of the Byronic hero - Cristina Ceron (Revue LISA)
The widespread popularity of Byron’s work during the Victorian age introduced several subversive possibilities for reading his characters as icons of transgression and insights into the literary tabooed. For Victorian novelists, one of the most intriguing aspects of his works was his obsessive explorations of literal or symbolic sibling incest, as the possibility that desire arises from an identification between male and female versions of the same psyche. Emily Brontë’s reading of Byron privileges this dark side of the literary myth, and her main focus is on the mysterious identity and Gothic aspects of the Byronic hero. Even though several critics have actually labelled the character of Heathcliff as ‘Byronic hero’, the debate has not delved into the textual or thematic evidence of the relation between Brontë’s protagonist and Byron hypertexts. My paper aims at investigating Brontë’s reading of Byron’s works, in particular her indebtedness to Manfred and to the relationship between Manfred and Astarte for the creation of the morbid passion experienced by  Heathcliff and Catherine. The study will concentrate on Brontë’s appropriation and emphasis on the Gothic elements presented in nuce in Manfred, such as the spectral nature of Astarte, or the supernatural aspects of Manfred’s nature, whose will supersedes even Fate. My hypothesis is that Brontë makes use of these aspects of Byron’s characters with the precise aim of setting the Gothic element as alternative narrative mode, as the subversive element inside a realistic novel. On the contrary, in spite of some juvenile experiments on the gothic, Charlotte’s reading of the Byronic hero is much more framed within the conventions of the realistic novel, and in the second section of my essay I maintain that what comes to the fore in Jane Eyre is the unsurpassed mastery the novelist shows in the combination of the realistic plot with the gothic elements and features of the protagonists. Far from enacting mere Romantic passion, the relationship between Jane and Rochester, just like Catherine’s liaison with Heathcliff, follows the textual dynamics of the Gothic romance, in that the woman falls prey to the more or less demonic instincts of her lover, suffers from the violence of his feelings and at the end is entangled by his thwarted passion, even though when we read the domestic happy ending we tend to forget the gothic matrix of the story…